The molt of long-term economic development - Suwan-achariya, Chinnasak (National Interest, 2021)
The objective of the article is to examine the functional principles of the neoliberal economy in the midst of the coronavirus pandemic and find new economic types to enter recovery and the transition to a new economy. The study found that neoliberal market economies could not continue with their principles and duties because the cost of producing goods was dependent on state intervention and demand from government incentives, the financial sector could not create. Motivation can be longer with the long-term inflation, the division of international labor that creates an advantage is no longer necessary. This creates the concept of sufficiency that requires a more careful strategy of self-sufficiency and building a production chain. Budget incentives alone cannot tackle the problem as the epidemic is like a war to prevent panic. Calls on the state to intervene to protect the parts of the economy that are essential to life so that basic living conditions exist, requiring readiness for online platforms,information about mobilizing people, tools, resources to insure essential lifestyle factors. As these changes require a high level of professionalism, being able to respond quickly to information to expedite decision-making to correct fragile supply chains and to ensure employee sterility in the workplace, many intermediate jobs will be lost. As a result, wages do not increase and income inequality increases, replacing the composition with future GDP service share, allowing the economy to continue to grow.